Performance enhancement of the dual-metal gate In0.53Ga0.47As dopingless TFET by using a platinum metal strip insertion. (9th September 2019) - Liu, Hu; Yang, Lin-An; Chen, Yao; Jin, Zhi; Hao, Yue
Abstract: In this paper, a dual-metal gate In0.53 Ga0.47 As dopingless TFET with a platinum metal strip insertion (Pt-MSDG-TFET) is proposed and systematically investigated by using the numerical simulation. Different from that the hafnium metal strip directly reduces the lateral tunneling distance, the platinum metal strip shifts the tunneling junction toward the gate electrode, which obtains a smaller lateral tunneling distance through the applied gate voltage so as to more benefit the electron tunneling. Meanwhile, it makes the performance for Pt-MSDG-TFET more sensitive to the variation of tunneling gate workfunction (ΦM4 ), so that better DC and RF performances can be obtained with the decrease of ΦM4 . Moreover, the investigation on the misalignment of the metal strip contributes to give a direction for the practical feasibility of manufacturing. Research indicates that the proposed Pt-MSDG-TFET is a promising TFET for ultra-low power consumption RF application.